Nickel‐Catalyzed Thermal Redox Functionalization of C(sp3)−H Bonds with Carbon Electrophiles. (31st March 2022) - Gong, Yuxin; Su, Lei; Zhu, Zhaodong; Ye, Yang; Gong, Hegui
Abstract: C(sp 3 )−H bond coupling with carbon electrophiles remains rarely explored under thermo‐driven hydrogen atom transfer (HAT) conditions due to the challenge of integrating oxidation and reduction in a single operation. We report here a Ni‐catalyzed arylation and alkylation of C(sp 3 )−H bonds with organohalides to forge C(sp 3 )−C bonds by merging economical Zn and t BuOO t Bu (DTBP) as the external reductant and oxidant. The mild and easy‐to‐operate protocol enables facile carbofunctionalization of N‐/O‐α‐ and cyclohexane C−H bonds, and preparation of a few intermediates of bioactive compounds and drug derivatives. Preliminary mechanistic studies implied addition of an alkyl radical to a Ni II salt. Abstract : Under thermal conditions, nickel‐catalyzed C(sp 3 )−H redox functionalization with carbon electrophiles has been advanced to forge value‐added C(sp 3 )−C bonds in good to excellent efficiency. This method emphasizes the use of external Zn as reductant and di‐ tert ‐butyl peroxide as an oxidant and shows remarkable compatibility with Ni‐catalysis.